Industrial applications of lasers - Ready, John F., 1932-
A practical book with a variety of uses, this book can help applications engineers spark problem-solving techniques through the use of lasers. Industrial Application of Lasers, Second Edition takes the reader through laser fundamentals, unusual properties of laser light, types of practical lasers available, and commonly used accessory equipment. The book also applies this information to existing and developing applications. Current uses of lasers, including laser welding and cutting, electronic fabrication techniques, lightwave communications, laser-based applications in alignment, surveying, and metrology are all covered as well as discussing the potential for future applications such as all-optical computers,remote environmental monitoring, and laser-assisted thermonuclear fusion. Key Features * Explains basic laser fundamentals as well as emphasizing how lasers are used for real applications in industry * Describes the importance of laser safety * Discusses potentially important future applications such as remote environmental monitoring * Includes rare expert lore and opinion.